METHODS AND COMPOSITIONS OF MODULATING TUMOR INITIATING CELLS AND THE USE THEREOF (2014)
A therapeutic vector can include: a lipid particle; a CD44 antigen targeting moiety associated with the lipid particle; and a therapeutic nucleic acid associated with the lipid particle. The CD44 antigen targeting moiety can be anti-CD44 antibody and/or anti-CD44 scFv. The lipid particle can have a formula according to one of the following: DOTAP/DOPE 1:1 molar ratio; DDAB/DOPE 1:1 molar ratio; DDAB/DOPE 1:2 molar ratio; DOTAP/Chol 1:1 molar ratio; DDAB/Chol 1:1 molar ratio; DOTAP/DOPE/Chol 2:1:1 molar ratio; and DDAB/DOPE/Chol 2:1:1 molar ratio. The molar ratios can range +/−1%, 5%, 10%, or 20%. A method of inhibiting cancer development can include: providing the therapeutic vector and administering the therapeutic vector to the subject in an amount to inhibit cancer development.